Makna Diri dan Branding Fotografer - Yogascitra Naufal; Neni Yulianita; Anne Maryani (Program Studi Hubungan Masyarakat Politeknik LP3I, 2023)
The development of photography in the city of Bandung is closely related to the development of photography in Indonesia. Bandung is one of the big cities in Indonesia with a very rapid development of photography, especially with the emergence of various photographers with specialization in their fields. With the presence of many photographers who have started to appear in the city of Bandung, many photographers are still looking for the meaning of their photography activities and the branding that must be done so that the public becomes aware and uses their services. From this phenomenon, the research